2011
DOI: 10.1007/s00419-011-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent thermoelastic creep analysis of rotating disk made of Al–SiC composite

Abstract: Time-dependent creep stress redistribution analysis of rotating disk made of Al-SiC composite is investigated using Mendelson's method of successive elastic solution. All mechanical and thermal properties except Poisson's ratio are radial dependent based on volume fraction percent of SiC reinforcement. The material creep behavior is described by Sherby's constitutive model using Pandey's experimental results on Al-SiC composite. Loading is an inertia body force due to rotation and a distributed temperature fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Therefore, similarly to the work done by Loghman et al (2011), the disc parameter such as density, Poisson's ratio, thermal expansion coefficient and elasticity modulus can be calculated using a linear mixture rule which is presented by Eq. (4.4).…”
Section: Numerical Application and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, similarly to the work done by Loghman et al (2011), the disc parameter such as density, Poisson's ratio, thermal expansion coefficient and elasticity modulus can be calculated using a linear mixture rule which is presented by Eq. (4.4).…”
Section: Numerical Application and Discussionmentioning
confidence: 99%
“…Before providing the results of the FGM rotating disc, to validate the analysis and the developed computer code, the results of tangential strain rate have been computed for a disc which was used by Loghman et al (2011) and Ghorbani (2012). A comparison between the results is shown in Fig.…”
Section: Numerical Application and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the finite element method, Reddy and Huang [10] presented the large deflection bending of annular plates with variable thickness. Applying the Mendelson's method of successive elastic solution, Loghman et al [11] investigated the time-dependent creep stress redistribution analysis of rotating disk made of Al-SiC composite. Based on the J2 deformation theory, Hu [12] analyzed large deformation of the axisymmetric rotating disk.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, with perfect interface contact, the decreasing of the CNT radius would improve the overall stiffness and plastic strength, but with an imperfect interface the size effect was reversed. Time-dependent thermo-elastic creep analysis of a rotating disk made of Al-SiC composite using Mendelson's method of successive elastic solution was presented by Loghman et al (2011). They found that the stresses, displacement, and creep strains were changing with time at a decreasing rate so that after almost 50 years the solution approached the steady-state condition.…”
Section: Introductionmentioning
confidence: 99%